Management and outcome of clinically evident neck recurrence in patients with papillary thyroid cancer - Wang, Laura Y. (Clin Endocrinol (Oxf), 2017)
BACKGROUND: The aim of this study was to report our incidence of clinically evident neck recurrence, salvage neck management and subsequent outcomes in patients with papillary thyroid cancer. This is important to know so that patients with thyroid cancer can be properly councelled about the implications of recurrent disease and subsequent outcome. METHODS: An institutional database of 3664 patients with thyroid cancer operated between 1986 and 2010 was reviewed. Patients with non-papillary histology, gross residual disease and those with distant metastases at presentation or distant metastases prior to nodal recurrence were excluded from the study. Of these, 99 (3.0%) patients developed clinically evident nodal recurrence. Details of recurrence and subsequent therapy were recorded for each patient. Subsequent disease specific survival (sDSS), distant recurrence free survival (sDRFS) and nodal recurrence free survival (sNRFS) were determined from the date of first nodal recurrence using the Kaplan Meier method. RESULTS: Of the 99 patients, 59% were female and 41% male. The median age was 41 years (range 5–91). The majority of patients had pT3/4 primary tumors (63%) and were pN+ (78%) at initial presentation. The median time to clinically evident nodal recurrence was 28 months (range 3–264). Nodal recurrence occurred in the central neck in 15 (15%) patients, lateral neck in 74 (75%) patients and both in 10 (10%) patients. After salvage treatment, the 5 year sDSS was 97.4% from time of nodal recurrence. The 5 year sDRFS and sNRFS were 89.2% and 93.7% respectively. CONCLUSION: In our series, isolated clinically evident nodal recurrence occurred in 3.0% of patients. Such patients are successfully salvaged with surgery and adjuvant therapy with sDSS of 97.4% at 5 years.